Exploring the cause of the inhibitor 4AX attaching to binding site disrupting protein tyrosine phosphatase 4A1 trimerization by molecular dynamic simulation. Issue 18 (12th December 2019) - Wei-Ya, Li; Yu-Qing, Duan; Yang-Chun, Ma; Xin-Hua, Lu; Ying, Ma; Wang, Run-Ling
Abstract: Ectopic overexpression of protein tyrosine phosphatase of liver regeneration-1 (PTP4A1, also called PRL-1) markedly enhanced hepatocellular carcinoma (HCC) cells migration and invasion. The PTP4A1 trimerization played a vital role in mediating cell proliferation and motility. Biochemical and structural studies have proved that the compound 4AX, a well-known inhibitor for PRL1, directly binds to the PTP4A1 trimer interface and obstructs trimer formation of PTP4A1. However, the molecular basis of the ligand-4AX inhibition on PTP4A1 trimer conformations remains unclear. In this study, the docking analysis and the molecular dynamics simulation (MD simulation) study were performed to investigate how the molecule binding at each interface disrupted the trimer formation. The results suggested that the ligand-4AX attaching to the binding site changed the conformation of A:Q131, A:Q135 in the AC interface, C:R18, C:P96 in the CA interface and B:Q131 in the BA interface, leading to the weak interactions between subunits and thus resulting in the disruption of the PTP4A1 trimerization.